A common fixed point theorem for subcompatible mappings in fuzzy metric space - Jha, Kanhaiya (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The aim of the present paper is to establish a common fixed point theorem for subcompatible pair of self mappings in a fuzzy metric space which generalizes and improves various well-known comparable results. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. I, June, 2016, Page: 90-98